Blockchain Technology and Cryptocurrencies A Survey Report - Manjit Kaur (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Blockchain is a well-known distributed and decentralized digital ledger comprising of smart contracts which ensures secured transactions unlike traditional log maintenance approaches. Blockchain is a widely used applications in technology such as internet of things and pii using highly sophisticated initiatives like cryptography algorithms in a systematic manner. As blockchain is one of the most popular platforms which has transformed many of traditional technologies and provides more convenient approaches. It becomes necessary to evaluate security and privacy issues associated with it. The incorrect predictions may affect economically and socially. Traditional technologies in wall centralised management that leads to several cyber challenges eventually the blockchain platform has become more trustworthy because of it uses dedication connection between the communicating parties in terms of transaction as well as for end-to-end operation completion without the intervention of any third party. This paper can template the challenges and various aspects associated with security and privacy under this highly sophisticated platform while dealing with various cryptocurrencies.